Perbandingan Therapy Akupresure Dan Nafas Dalam Mengurangi Nyeri Persalinan Di Pmb Mursalina - Patimah, Titin; Putri , Maidina (Cattleya Darmaya Fortuna, 2023)
Labor pain in the first stage of the active phase is caused by adequate uterine contractions occurring 3-5 times in 10 minutes with contractions lasting between 30 and 60 seconds. The uterine contraction movement causes the muscles of the uterine wall to contract, clamping the blood vessels, the vagina and the surrounding soft tissue to stretch, resulting in pain. The mother's mental state (fear, anxiety, worry or tension) and the hormone prostaglandin increase in response to stress. The intensity of pain during the first stage of the active phase is caused by the strength of the contraction and the pressure generated. The greater the abdominal distension, the more severe the pain intensity. Pain can cause an increase in blood pressure, pulse, breathing, sweating, muscle tension and the mother's concentration during labor becomes disturbed. If the mother cannot endure the pain, all of this can have a bad effect on the smoothness of the birth resulting in a long labor.